166k views
3 votes
Write the equation of the graph shown below in the factored form f(x) = (x + 2) (x - 1) (x - 3) f(x) = (x - 2) (x + 1) (x + 3) f(x) = (x + 2) (x + 1) (x + 3) f(x) = (x - 2) (x - 1) (x - 3)

Write the equation of the graph shown below in the factored form f(x) = (x + 2) (x-example-1
User Tjac
by
4.9k points

1 Answer

2 votes

Answer:


f(x)=(x-1)\,(x-3)\.(x+2)

which agrees with the first answer shown in the list of possible options.

Explanation:

Notice that there are three roots for this polynomial clearly shown on the graph's crossings of the x axis: x = 1, x = 3, and x = -2.

Therefore, based on such, we can write three binomial factors of the form
(x-root) for the polynomial:


f(x)=(x-1)\,(x-3)\.(x-(-2))=(x-1)\,(x-3)\.(x+2)

User Jasperan
by
4.8k points